PERICARDITIS: ETIOLOGY, CLASSIFICATION, CLINIC, DIAGNOSTICS, TREATMENT. PART I - A.B. Sugak ("Paediatrician" Publishers LLC, 2009)
Pericarditis is relatively widespread inflammatory disease of pericardium. Symptoms of this disease was described already in the beginning of XIXth century, but it's clinical diagnostics in patient's lifetime is difficult up to now. Majority of acute pericardites have favorable clinical course, but some of them have complications (cardiac tamponade and constrictive pericarditis), which are potentially lethal. Development of non-invasive radiation methods of heart visualization technologies improved diagnostics of pericarditis in last years. Besides, achievements of immunology, virology and microbiology allowed widening of data of etiology and pathogenesis of pericardial diseases. Present lecture gives modern data of etiology, classification, clinical signs, diagnostics and treatment of pericarditis. The description of separate specific types of pericardites is given. Key words: children, pericarditis. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):77-84)